2020
DOI: 10.1371/journal.pone.0239975
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the PI-RADS 2.1 scoring system to PI-RADS 2.0: Impact on diagnostic accuracy and inter-reader agreement

Abstract: To assess the value of the PI-RADS 2.1 scoring system in the detection of prostate cancer on multiparametric MRI in comparison to the standard PI-RADS 2.0 system and to assess its inter-reader variability. Materials and methods This IRB-approved study included 229 patients undergoing multiparametric prostate MRI prior to MRI-guided TRUS-based biopsy, which were retrospectively recruited from our prospectively maintained institutional database. Two readers with high (reader 1, 6 years) and low (reader 2, 2 year… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 27 publications
(14 citation statements)
references
References 20 publications
0
13
0
1
Order By: Relevance
“…The mean patient age was 63.1-73 years and with a PSA level of 4.9-13.7 ng/ml. Regarding zonal anatomy, 5 studies reported the inter-reader agreement only for TZ ( 27 , 30 , 31 , 33 , 34 ), 2 studies reported the inter-reader agreement both for TZ and PZ ( 24 , 32 ), 4 studies reported the reproducibility for the whole gland and did not differentiate location ( 25 , 26 , 28 , 35 ), only 1 study reported the inter-reader agreement merely on PZ lesions ( 29 ). In 4 studies the MRI images were interpreted by 2 radiologists ( 28 , 29 , 31 , 34 ), whereas in the remaining 8 studies the MRI images were interpreted by at least 3 radiologists.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The mean patient age was 63.1-73 years and with a PSA level of 4.9-13.7 ng/ml. Regarding zonal anatomy, 5 studies reported the inter-reader agreement only for TZ ( 27 , 30 , 31 , 33 , 34 ), 2 studies reported the inter-reader agreement both for TZ and PZ ( 24 , 32 ), 4 studies reported the reproducibility for the whole gland and did not differentiate location ( 25 , 26 , 28 , 35 ), only 1 study reported the inter-reader agreement merely on PZ lesions ( 29 ). In 4 studies the MRI images were interpreted by 2 radiologists ( 28 , 29 , 31 , 34 ), whereas in the remaining 8 studies the MRI images were interpreted by at least 3 radiologists.…”
Section: Resultsmentioning
confidence: 99%
“…Regarding zonal anatomy, 5 studies reported the inter-reader agreement only for TZ ( 27 , 30 , 31 , 33 , 34 ), 2 studies reported the inter-reader agreement both for TZ and PZ ( 24 , 32 ), 4 studies reported the reproducibility for the whole gland and did not differentiate location ( 25 , 26 , 28 , 35 ), only 1 study reported the inter-reader agreement merely on PZ lesions ( 29 ). In 4 studies the MRI images were interpreted by 2 radiologists ( 28 , 29 , 31 , 34 ), whereas in the remaining 8 studies the MRI images were interpreted by at least 3 radiologists. Regarding readers’ experience, 5 studies reported that the MRI images were interpreted by experienced or dedicated radiologists ( 25 , 27 , 31 , 34 , 35 ), whereas in the remaining 7 studies the images were interpreted by radiologists with varied experience (1-20 years).…”
Section: Resultsmentioning
confidence: 99%
“…[15] These findings were also supported for PZ lesions in the study of Bhayana et al [16] They found that interreader agreement was higher in PI-RADSv2.1 (kappa = 0.64) than PI-RADSv2 (kappa = 0.51). Unlikely, Hötker et al [17] claimed that interreader agreement was higher in the former version (Kappa = 0.57 for PI-RADSv2 and Kappa = 0.51 for PI-RADSv2.1). But the difference of experience between the readers was higher in this study.…”
Section: Discussionmentioning
confidence: 91%
“…Therefore, multi-institutional studies with image interpretation data of multiple radiologists are needed to confirm the generalizability of our results. Recent studies have reported that the interreader agreement was moderate or good (kappa, 0.51-0.64) for interpreting PI-RADSv2.1 [37][38][39] and excellent (concordance correlation coefficient, >0.80) for ADCR, 32 respectively. External validation studies are needed to test the feasibility of the nomogram despite some variabilities in MRI interpretation.…”
Section: Limitationsmentioning
confidence: 99%